Searching for innovation in market and transition economies: evidence across Europe - Wolfgang Sofka; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Searching for externally available knowledge has been characterized as a vital part of the innovation process. The availability of such innovation impulses, however, critically depends on the environment a firm is operating in. Little is known on how institutional infrastructures for innovation differ with respect to the munificence in providing innovation impulses. In this paper, we suggest that these differences are particularly pronounced between established market economies and transition economies. We argue that these differences shape a firm's search pattern and that the search pattern subsequently moderates the relationship between innovation inputs and outputs. Based on a sample of more than 4,500 firms from ten European countries we find that search strategies differ considerably between established market and transition economies. Search in transition economies is characterized by much more variety. However, management capacity in these countries is a particularly scarce resource which is why focused search strategies turn out to be most successful.
Keywords: L60; O32; 330; Search strategies; open innovation; transition economies; institutional infrastructure for innovation; Innovation; Wissenstransfer; Informationsverhalten; Suchtheorie; Vergleich; Übergangswirtschaft; Osteuropa; Westeuropa